Italian Renaissance humanism in the mirror - Baker, Patrick 1976- (Cambridge University Press, 2015)
This important study takes a new approach to understanding Italian Renaissance humanism, based not on scholarly paradigms or philosophical concepts but on a neglected yet indispensable perspective: the humanists' understanding of themselves. Through a series of close textual studies, Patrick Baker excavates what humanists thought was important about humanism, how they viewed their own history, what goals they enunciated, what triumphs they celebrated - in short, he attempts to reconstruct humanist identity. What emerges is a small, coherent community dedicated primarily not to political ideology, a philosophy of man, an educational ethos, or moral improvement, but rather to the pursuit of classical Latin eloquence. Grasping the significance this stylistic ideal had for the humanists is essential to understanding both their sense of themselves and the importance they and others attached to their movement. For eloquence was no mere aesthetic affair but rather appeared to them as the guarantor of civilisation itself
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte; Renaissance / Italy; Humanism / Italy / History; Eloquence in literature; Latin language; Stil; Identität; Renaissance; Latein; Humanist; Italien